Laparoscopic low anterior resection of rectum: A case report with review ofliterature (Indian Journal of Case Reports, 2024)
Low anterior resection (LAR) is the standard operative treatment for rectal cancer. Laparoscopic anterior resections were first attempted in the 1990s. With the passage of time, laparoscopic instrumentation, energy sources, and laparoscopic techniques underwent a significant improvement. With all the above advancements, at the turn of the 20th century, there emerged strong evidence in the literature in favor of laparoscopic therapy for rectal cancer. Large-volume multicenter studies, various randomized controlled trials, and many review analyses of large databases, for example, Cochrane; conclusively showed that laparoscopy was not inferior to open surgery in oncological completeness of the resection; in colorectal cancer. Given its cosmetic superiority, lesser post-operative pain, and earlier resumption of routine day-to-day activity, laparoscopic radical colorectal cancer surgery has become standard practice in advanced laparoscopic health-care setups all over the world. Herein, we present the case of a 77-year-old gentleman who was diagnosed with low rectal cancer, underwent a laparoscopic LAR, and is disease-free until date, on serial surveillance investigations; over a post-operative follow-up period of just over 9 years.